Genetic Variations of Echinococcus granulosus Isolated from Sheep and Cows by Using Fingerprint DNA Method in Iraq - Zaman A.A. Ibrahim; Salwa S.Muhsin; Farhan A. Risan (College of Pharmacy University of Baghdad, 2017)
The fingerprinting DNA method which depends on the unique pattern in this study was employed to detect the hydatid cyst of Echinococcus granulosus and to determine the genetic variation among their strains in different intermediate hosts (cows and sheep).  The unique pattern represents the number of amplified bands and their molecular weights with specialized sequences to one sample which different from the other samples.   Five hydatitd cysts samples  from cows and sheep were  collected, genetic analysis for  isolated DNA was done using PCR technique and  Random Amplified Polymorphic DNA reaction(RAPD) depending on (4) random primers, and the results showed:         1-Ability of OPF-13 primer to find fingerprinting for DNA of hydatid cysts collected from cows with       (3) unique patterns and from sheep with (5) unique patterns. 2- Ability of OPF-06 primer to found (4) unique patterns for cows and (2) unique patterns for sheep. 3-Ability of OPF-19 primer to find fingerprinting for DNA of hydatid cysts collected                                  from cows (5) unique patterns and (4) unique patterns for sheep. 4-OPF-16 was unable to find the finger prints of DNA isolated from cows and sheep Keywords : Hydatid cyst. OPF Primer .PCR.  RAPD.